5G User Plane Load Simulator - DÜSTERDIECK, OLOF; HUDA, TASDIKUL (My University, 2021)
As the commercial introduction of 5G networks is getting closer, the deployment of testing technology able to perform at the requirements specified for 5G, is of utmost importance. As a company on the leading edge of 5G deployment, Ericsson manages mobile traffic by developing a gateway known as the Evolved Packet Gateway (EPG). EPG is the main component responsible for bridging the gap for data packets between 5G base stations and servers on the Internet. Following the 5G design, EPG is split into a Control Plane (CP) and a User Plane (UP). The purpose of this thesis is to implement a 5G network simulator that is able to load test a physical 5G User Plane which is used to route traffic in a mobile network. The simulator is able to simulate traffic in both the uplink and downlink direction as well as sending traffic on several different user sessions. To simulate traffic, three different traffic models, steady-rate, step-wise rate and Poisson processes, are used. In each simulation, the traffic is stateless and follows a client-to-server architecture. All parts included in this architecture is simulated, except for the UP. To analyze the results of a test, we define several different performance metrics such as throughput and latency. These are evaluated using evaluation techniques such as Control Charts. Several sets of experiments are performed in which we verify the implemented load types and measure the maximum rate of both the simulator and the UP. Using these results, it is possible to analyze the scalability of the UP and our simulator. We conclude that our simulator performs above the required rate to load test the UP for most scenarios with differing number of users and flows per each user. Where this is not the case, ideas and suggestions on how the simulator can be enhanced additionally are given. We also conclude that the UP scales very well with an increased number of users and that it performs above the proposed 5G requirements.
Keywords: 5G; EPG; User Plane; load testing; mobile networking; network simulator; traffic modeling